Teacher and Student Perceptions on the Use of Differentiated e-LKPD in Project-Based Learning on Organic Waste Processing to Improve Critical Thinking Skills - Umamah Apriyanti; Chansyanah Diawati; M. Setyarini (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to determine the perception of science teachers towards differentiated electronic student worksheets based on organic waste processing projects to improve critical thinking skills. The research method used is a qualitative method. Data collection techniques through questionnaires and interviews, then analyzed using descriptive analysis. The questionnaire was distributed to 10 science teacher respondents and 96 junior high school students in South Lampung Regency. The results showed that 80% of teachers had not used differentiated electronic student worksheets based on projects and had not trained critical thinking skills; according to students, no teachers implemented project-based learning. Based on the results of the study, it can be concluded that differentiated e-LKPD based on organic waste processing projects is needed to improve students' critical thinking skills.